Detection of adulteration in virgin coconut oil using instrumental methods and preliminary sensory profiling - Tampil, Gyle D. (College of Home Economics, University of the Philippines Diliman, 2020)
Detection of adulteration in Philippine virgin coconut oil (VCO) using refined, bleached, and deodorized (RBD) coconut oil and mineral oil (MIN) as adulterants was studied using instrumental methods and preliminary sensory profiling. The study aimed to differentiate instrumental color and viscosity properties of unadulterated and adulterated VCO samples, generate preliminary sensory profiles for both samples, and conduct preliminary correlation between gathered instrumental data and sensory data. Yellowness index (YI) did not show any significant differences (p<0.05) even at 50% for both adulterants. Evaluation of total color differences (ΔE) detected RBD-adulteration at 50% concentration while no color difference was detected in MIN-adulterated samples. Viscosity values (mPa·s) of MIN-adulterated samples showed a significant difference (p<0.05) starting at 20% adulteration and was able to detect adulteration from said concentration, while RBD-adulterated samples did not show significant differences. A total of 9 terms were generated and validated by 7 trained panelists to describe and differentiate adulterated and unadulterated samples. The panel was not able to detect differences in the sensory properties of RBD- and MIN- adulterated samples except for yellow color of samples with >20% RBD. Preliminary correlations showed very high positive correlations between yellowness index and yellow scores (r=0.9588; p<0.05), and between total color difference and yellow scores (r=0.9532; p<0.05), while negligible correlation was observed for viscosity values with mouthfeel and skin feel ratings of the VCO samples.